3D‐to‐2D Dimensional Reduction for Exploiting a Multilayered Perovskite Ferroelectric toward Polarized‐Light Detection in the Solar‐Blind Ultraviolet Region. (17th September 2020) - Xu, Zhiyun; Weng, Wen; Li, Yaobin; Liu, Xitao; Yang, Tao; Li, Maofan; Huang, Xiaoying; Luo, Junhua; Sun, Zhihua
Abstract: Polarized‐light detection in solar‐blind ultraviolet region is indispensable for optoelectronic applications, whereas new 2D candidates targeted at solar‐blind UV range remain extremely scarce. 2D hybrid perovskite ferroelectrics that combine polarization and semiconducting properties are of increasing interest. Here, using the 3D‐to‐2D dimensional reduction of CH3 NH3 PbCl3, we designed a multilayered hybrid perovskite ferroelectric, (CH3 CH2 NH3 )2 (CH3 NH3 )2 Pb3 Cl10, which shows spontaneous polarization and a high Curie temperature (390 K) comparable with that of BaTiO3 (393 K). The wide band gap (ca. 3.35 eV) and anisotropic absorbance stemming from its intrinsic 2D motif, greatly favor its polarization‐sensitive activity in UV region. The device displays excellent polarization‐sensitive behavior under 266 nm, along with a large dichroic ratio (ca. 1.38) and high on/off current ratio (ca. 2.3×10 3 ). Abstract : A multilayered perovskite ferroelectric, (EA)2 (MA)2 Pb3 Cl10, was designed by 3D‐to‐2D dimensional reduction. The fascinating attributes including wide band gap and anisotropic optical absorbance, account for its polarization‐sensitive response in solar‐blind ultraviolet region.